Astrocytes as a target for therapeutic strategies in epilepsy: current insights - Çarçak, Nihan; Onat, Filiz; Sitnikova, Evgenia (Frontiers in Molecular Neuroscience, 2023)
Astrocytes are specialized non-neuronal glial cells of the central nervous system, contributing to neuronal excitability and synaptic transmission (gliotransmission). Astrocytes play a key roles in epileptogenesis and seizure generation. Epilepsy, as a chronic disorder characterized by neuronal hyperexcitation and hypersynchronization, is accompanied by substantial disturbances of glial cells and impairment of astrocytic functions and neuronal signaling. Anti-seizure drugs that provide symptomatic control of seizures primarily target neural activity. In epileptic patients with inadequate control of seizures with available anti-seizure drugs, novel therapeutic candidates are needed. These candidates should treat epilepsy with anti-epileptogenic and disease-modifying effects. Evidence from human and animal studies shows that astrocytes have value for developing new anti-seizure and anti-epileptogenic drugs. In this review, we present the key functions of astrocytes contributing to neuronal hyperexcitability and synaptic activity following an etiology-based approach. We analyze the role of astrocytes in both development (epileptogenesis) and generation of seizures (ictogenesis). Several promising new strategies that attempted to modify astroglial functions for treating epilepsy are being developed: 1) selective targeting of glia-related molecular mechanisms of glutamate transport; 2) modulation of tonic GABA release from astrocytes; 3) gliotransmission 4) targeting the astrocytic Kir4.1-BDNF system; 5) astrocytic Na+/K+/ATPase activity; 6) targeting DNA hypo- or hypermethylation of candidate genes in astrocytes; 7) targeting astrocytic gap junction regulators; 8) targeting astrocytic adenosine kinase (the major adenosine-metabolizing enzyme); 9) targeting microglia-astrocyte communication and inflammatory pathways. Novel disease-modifying therapeutic strategies have now been developed, such as astroglia-targeted gene therapy with a broad spectrum of genetic constructs to target astroglial cells.